(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2019)
The article presents the main legal challenges emerging from the profound changes that the field of biomedical research underwent in recent years. The shift of focus on biological samples and data, the impact of new technologies producing huge amount of data, difficult to be interpreted and processed, the global dimension of research activities and the consequent importance of sharing samples and data and to make them widely accessible represent a fundamental test for the law. The paper critically describes the normative framework designed by the GDPR and the Italian legislation to balance the need to protect participants and the importance of fostering biomedical research. The proposed strategy, giving-up of the "oppositional" point of view and promoting consonances, aims at relaxing the specificity of consent while integrating it with specific requirements to encourage the concept of a responsible research.